Enhancing waste resource efficiency: circular economy for sustainability and energy conversion - Elroi, Hadad; Zbigniew, Grzymala; Agnieszka, Wójcik-Czerniawska; Piotr, Szewczyk (Frontiers in Environmental Science, 2023)
This study explores optimizing waste resource efficiency through the Circular Economy (CE) framework. Motivated by the imperative to enhance resource efficiency and mitigate waste's environmental impact, we examine the CE concept's extension of product life cycles, while minimizing waste. We conduct a comprehensive review to explore the core CE principles across all stages of the product lifecycle and provide an in-depth analysis of waste treatment practices in Poland, emphasizing potential energy conversion methods like biogas production and incineration. Our findings underscore the importance of prioritizing waste incineration plant design for quicker payback, aligning with circular rational economic practices. Strategies such as improving biogas production, establishing solid bio-waste fermentation facilities, promoting sortable packaging, and incentivizing sustainable sorting emerge to optimize waste management. These findings highlight the pivotal role of economic, environmental, and energy considerations in shaping sustainable waste management strategies.